Kajian fenomenologi pemasaran digital agen properti melalui medium instagram - Ernayani, Rihfenti; Daengs GS, Achmad; Tarigan, Nuah P.; Lestari, Winda; Timotius, Elkana (Jurnal Komunikasi Profesional, 2021)
Property has developed into a basic human need that everyone wants to have personally. Property is used for investment other than for basic human needs. The Covid-19 pandemic began in March 2020, resulting in the imposition of large-scale social restrictions (PSBB) to stop the spread of the virus. The Coronavirus Disease (Covid-19) pandemic has also paralyzed a number of industries, including the real estate sector, in an effort to support economic growth. The purpose of this study is to determine the digital marketing of property agents on Instagram. This study uses a qualitative approach with the phenomenological method of the actors in the property business agent. The results showed that digital marketing of property agents on Instagram is used with several efforts including the use of hashtags, collaborating with influencers and public figures, and giving giveaways to attract the interest of potential consumers.